2018
DOI: 10.7748/nop.2018.e1007
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to developing student placements in care homes

Abstract: If high quality person-centred care is to be provided for older people with complex needs, it is essential that nurse education should aim to extend students' knowledge and skills in long-term care, and integrated health and social care. Northumbria University, local care homes and NHS organisations have collaborated to develop integrated, cross-sector practice placements that support this learning for student nurses. While there have been challenges in developing these placements, initial feedback is positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While few papers have addressed this topic, Tiplady et al (2018) reported on a collaborative placement model between a UK university, care homes and the National Health Service (NHS). The study found the interorganisational working and learning beneficial to both the students and mentors.…”
Section: Introductionmentioning
confidence: 99%
“…While few papers have addressed this topic, Tiplady et al (2018) reported on a collaborative placement model between a UK university, care homes and the National Health Service (NHS). The study found the interorganisational working and learning beneficial to both the students and mentors.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates the embedding of older people nursing in settings such as care homes in responsive curricula and education programmes, including practice placements, and there are examples of this occurring internationally e.g. Finland (Kiljunen et al 2019), Australia (Loffler et al 2018), the Netherlands (Snoeren et 2016) and in the UK (Tiplady et al 2018). However, in the UK, student nurses in Higher Education Institutions (HEI) receive the majority of their clinical placement learning in acute care nursing (Spilsbury et al 2015).…”
Section: Introductionmentioning
confidence: 99%